Geopoetics of the North: The Literature of the Indigenous Peoples of the North of Yakutia - Burtseva, Zhanna Valer'evna (Journal of History Culture and Art Research, 2018)
In the literature of the Indigenous Peoples of the North of Yakutia, the conceptual role is played by the image of the North, which is advisable to consider in the mainstream of geopoetics or poetics of space, revealing the regional picture of the world and the cultural landscape. In a general sense, geopoetics is thought of as a mental, intellectual, and artistic development of geographical space by man. In the study, we focus on the fact that the North in the literature of Yakutia is a cultural mental category, a unique space, in the aspect of the presence of real spatial components and those imaginative mythopoetic connotations that this space is endowed with. In this regard, the unique natural parameters of the North, its cultural and historical specificity, give reason to assert, first of all, the existence of the Northern text of Yakutia’s literature, a special semiotic space, and second of all, the Northern text is more a phenomenon not thematic, but mental, because it reflects a special version of the ethnic picture of the world. The study of this regional Northern text will allow us to outline the broad possibilities of comparative historical and typological research. The Northern text in the literature of Yakutia became the most representative in the second half of the 20th century, it is caused and formed by literary and extra-literary factors, is revealed in all semiotic systems. Its semantic core is the literature of small-numbered peoples of the North on the basis of characteristic themes, key images-concepts and symbolic motives. Literature of the indigenous peoples of the North of Yakutia includes literature of Yukaghir, Evens, Evenks people, which have different cultural and philosophical, historical and genetic roots, but also have territorial, contact-typological, ethnic unity. Semiotic space in literary texts representing the North, is represented mainly in the generalized historical-philosophical and natural-philosophical character, landscape-geographical and mythological uniqueness of the Northern region.